Eco-friendly water treatment: The role of MIL metal-organic frameworks for the bisphenols adsorption from water - Mahmad, Afzan; Noh, Teh Ubaidah; Khalid, Nurul Izzah (Elsevier, 2023)
Achieving the Sustainable Development Goals (SDGs) 2023 required prioritizing the reduction of water pollution, including bisphenols pollution, in order to protect the environment and human health. Metal ˆ’ organic frameworks (MOFs), specifically MILs (MIL = Material Institute of Lavoisier), acquired recognition as promising materials for bisphenols adsorption because of their adaptability and unique properties. This review summarized the recent updates of knowledge on MILs, including an overview of bisphenols in wastewater environments and MILs MOFs, synthesis techniques, mechanisms, equilibrium, kinetic modelling and thermodynamic studies, the effect of pH and ionic strength, regeneration/reusability studies, the feasibility of MILs MOFs as well as challenges and prospects for bisphenols adsorption. However, further research was needed to understand the mechanisms and relationships underlying MILs and enable their practical, commercial ˆ’ scale use in bisphenols remediation. This review highlighted the growing importance of MILs MOFs in environmental applications and the necessity in green technologies for substantial remediation.